2014
DOI: 10.5009/gnl13327
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Using Simulated Targets in the Stomachs of Live Pigs for Full Endoscopic Submucosal Dissection Training

Abstract: Background/AimsIn endoscopic submucosal dissection (ESD) training, only a flat target lesion can usually be simulated in the normal mucosa. This study aimed to evaluate the feasibility of simulated targets in the stomachs of live pigs for complete training.MethodsSix trained endoscopists with hands-on experience with ex vivo, isolated pig stomachs were enrolled in this pilot study. An endoscopic banding device was used to create a polyp that was snared, leaving an ulcerated lesion. This simulated target model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Our model would have to be improved. As already described, creating simulated ulcerated target lesions, closer to those found in real life, can be a good way to add difficulty and to realise a new step in preclinical training 18 . After all, it is clear that this type of session is not sufficient in terms of efficiency but above all safety.…”
Section: Discussionmentioning
confidence: 98%
“…Our model would have to be improved. As already described, creating simulated ulcerated target lesions, closer to those found in real life, can be a good way to add difficulty and to realise a new step in preclinical training 18 . After all, it is clear that this type of session is not sufficient in terms of efficiency but above all safety.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, prior to training, the novice has never performed any of the techniques necessary for the performance of ESD such as lesion marking, mucosal pre-cutting, submucosal dissection, and hemostasis of the submucosal vessels. Animal models, both ex vivo and in vivo [ 8 10 ], are expensive, inconvenient, and time consuming. The expense of hands-on training with live animals may limit the ability of some training programs to provide ESD training.…”
Section: Discussionmentioning
confidence: 99%
“…The expense of hands-on training with live animals may limit the ability of some training programs to provide ESD training. One animal training session may cost nearly $300 (US) per trainee [ 10 ]. Additionally, the animal must be sacrificed afterward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the mid‐1990s, the simulator had been widely used in much hands‐on training programs . Studies have demonstrated the benefits of computer simulation for training in endoscopy, with reductions in the need for instructor assistance and patient discomfort and acceleration of new skills .…”
Section: Introductionmentioning
confidence: 99%